Analysis of the ethical aspects of professional confidentiality in dental practice (Journal of Applied Oral Science, 2008)
From the point of view of deontological ethics, privacy is a moral right that patients are entitled to and it is bound to professional confidentiality. Otherwise, the information given by patients to health professionals would not be reliable and a trustable relationship could not be established. The aim of the present study was to assess, by means of questionnaires with open and closed questions, the awareness and attitudes of 100 dentists working in the city of Andradina, São Paulo State, Brazil, with respect to professional confidentiality in dental practice. Most dentists (91.43%) reported to have instructed their assistants on professional confidentiality. However, 44.29% of the interviewees showed to act contradictorily as reported talking about the clinical cases of their patients to their friends or spouses. The great majority of professionals (98.57%) believed that it is important to have classes on Ethics and Bioethics during graduation and, when asked about their knowledge of the penalties imposed for breach of professional confidentiality, only 48.57% of them declared to be aware of it. Only 28.57% of the interviewees affirmed to have exclusive access to the files; 67.14% reported that that files were also accessed by their secretary; 1.43% answered that their spouses also had access, and 2.86% did not answer. From the results of the present survey, it could be observed that, although dentists affirmed to be aware of professional confidentiality, their attitudes did not adhere to ethical and legal requirements. This stand of health professionals has contributed to violate professional ethics and the law itself, bringing problems both to the professional and to the patient.